Developmental Change in the ERP Responses to Familiar Faces in Toddlers with Autism Spectrum Disorders Versus Typical Development - Webb, S.J. (2011)
Individuals with ASD show differences in face processing abilities from early in development. To examine whether these differences reflect an atypical versus delayed developmental trajectory, neural responses to familiar and unfamiliar faces in 24 18-to 47-month-old children with ASD were compared to responses of 32 12- to 30-month-old typically developing children. Results of two experiments revealed that neural responses to faces in children with ASD resembled those observed in younger typically developing children, suggesting delayed development. Electrophysiological responses to faces were also related to parent-report of adaptive social behaviors for both children with ASD and typical development. Slower development of the face processing system in ASD may be related to reduced self-directed ‘expected’ experience with faces in early development.